Rancang Bangun Sistem Informasi Monitoring dan Evaluasi Kinerja Field Collector pada PT Chrismalis Artha - Faristia, Fitriana; Sudarmaningtyas, Pantjawati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Chrismalis PT Artha is a company engaged in the credit card collection services provider. Field collection subdivision has responsibility to performing the field collection process to credit card customer. Based on observations and interviews, the main problem of field collection subdivision is field collectors doesn’t achieving the performance targets because of monitoring delays, evaluation errors and decision-making mistake.To solve these problems then be made of information systems solutions that can do the performance monitoring and evaluating process of field collector using web-based to reduce errors in the evaluation, optimize  customer handling and field collectors can achieving the target. Based on the results of the field collector performance monitoring and evaluation information system then the conclusion is the application indicate conformity with the expectation and feasible for use